Evaluasi Tingkat Kesiapan Keamanan Informasi Menggunakan Indeks Kami 4.2 dan ISO/IEC 27001:2013 (Studi Kasus : Diskominfo Kabupaten Gianyar) - Dicky Insan Khamil (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Dinas Komunikasi dan Informatika or Diskominfo of Gianyar Regency has the task of assisting the Regent in carrying out policies in the communication and informatics, including managing and securing information in running the local government according to the Gianyar Regional Regulation Number 5 of 2016. Referring to the Regulation of Kemenkominfo Number 4 of 2016, concerning the Information Security Management System, the Electronic System Operator must implement security for public interest information, public services, state defense, and security. Diskominfo Gianyar must implement and pay attention to information security which is managed as Electronic System Operator. This study evaluates information security which refers to the BSSN regulation Number 8 of 2021 regarding the Use of the KAMI Index as a standard evaluation tool to evaluate the Readiness Level of information security to maintain confidentiality, authenticity, integrity, and denial of information. This study uses the latest version of the KAMI Index, Version 4.2. Results from the evaluation will be compared with ISO/IEC 27001:2013 Control to obtain recommendations for improvement. Based on the results from the evaluation, Diskominfo Gianyar received a Final Score of 190 with a Readiness Level Status of "Not Eligible" to meet the ISO/IEC 27001 Standard.